Implementasi Project-Based Learning dalam Meningkatkan Prestasi Belajar Peserta Didik Sekolah Dasar - Darsinih Darsinih; Enas Enas; Asep Budi Tauhid (CV. ALIM'SPUBLISHING, 2026)
This study aims to describe and analyze the implementation of Project-Based Learning (PjBL) in improving elementary school students’ learning achievement in the Education Coordination Area (Korwil) of Rajadesa District, Ciamis Regency. The study employed a qualitative approach using a case study method to obtain an in-depth understanding of the planning, implementation, and evaluation of project-based learning. The research subjects consisted of principals, teachers, students, and school supervisors involved in the learning process. Data were collected through observation, in-depth interviews, and documentation studies. The data were analyzed using the interactive analysis model of Miles and Huberman, including data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation, technique triangulation, and member checking. The findings revealed that the implementation of PjBL was carried out through three main stages: planning, collaborative implementation, and authentic assessment. PjBL was proven to improve students’ cognitive, affective, and psychomotor learning achievement, as well as enhance critical thinking, communication, collaboration, and creativity skills. The novelty of this study lies in the contextual PjBL implementation model based on local characteristics that integrates collaborative, contextual, and reflective learning aspects into a unified learning cycle.